2019
DOI: 10.1186/s40792-019-0566-0
|View full text |Cite
|
Sign up to set email alerts
|

Aortoenteric fistula following overlap esophagojejunal anastomosis using linear staplers for cancer of the esophagogastric junction: a case report

Abstract: BackgroundAortoenteric fistula (AEF), occasionally reported as a fatal complication after aortic or other vascular procedures, is a communication between the aorta and the digestive tract. AEF as a fatal complication of overlap esophagojejunostomy after esophagogastrectomy has not been reported previously. Herein, we report a case of AEF after laparoscopic proximal gastrectomy and transhiatal lower esophagectomy for cancer of the esophagogastric junction, in which linear staplers were used for overlap esophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Covering the esophagojejunal anastomosis with an omentum flap might be a considerable strategy. 5 This is a case of post-esophagojejunostomy AEF who survived more than 2 years. A three-stage hybrid strategy is safe and feasible to manage fatal secondary AEF, as follows:…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Covering the esophagojejunal anastomosis with an omentum flap might be a considerable strategy. 5 This is a case of post-esophagojejunostomy AEF who survived more than 2 years. A three-stage hybrid strategy is safe and feasible to manage fatal secondary AEF, as follows:…”
Section: Discussionmentioning
confidence: 97%
“…3 By contrast, only two patients with post-esophagojejunostomy aortoesophageal fistula were reported. 4,5 The survivor, reported by Okita et al, 4 underwent primary closure and TEVAR to manage AEF, which occurred 24 days after esophagogastrectomy and alimentary reconstruction using a free jejunal graft. The other case, reported by Honda et al, 5 died 11 days after esophagogastrectomy, and the diagnosis of AEF was confirmed on autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors, including damage to the vasculature and perivascular nerve plexus in the vascular skeletonization process during lymphadenectomy, injury of the adventitia resulting from inappropriate use of the medical electric knife and ultrasound knife, and damage to the endarterium caused by ligation using inapposite sutures or crude clamping with vascular forceps, can result in chronic formation of pseudoaneurysm [3]. Furthermore, injury of the arterial wall resulting from postoperative persistent friction between the staple lines and bare arterial wall and perioperative radiotherapy has also been reported as a cause of pseudoaneurysm formation [911]. In general, rupture of the pseudoaneurysm mostly leads to intra-abdominal bleeding, and rupture into the gastrointestinal tract is rarely reported [5].…”
Section: Discussionmentioning
confidence: 99%